PERANCANGAN SISTEM Perancangan Sistem Informasi Keuangan Dan Penggajian Karywan Berbasis Web Menggunakan Framework LaravelINFORMASI KEUANGAN DAN PENGGAJIAN KARYAWAN BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL - Anjas Setiawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Financial Information System is an information system designed to provide information regarding the flow of money for users throughout the company. Financial information systems are used to support financial managers in making decisions concerning company financial matters and the allocation and control of financial resources within the company. However, not all companies implement a computerized financial and payroll system. Outlet Pertashop 3P16107 Bantajati is one of the companies that still uses a manual system in financial management and employee payroll. This method is not yet effective and efficient. Therefore the use of financial system applications and employee payroll is an alternative solution in managing financial reports for management. This research is based on system analysis, system design, and implementation using the Laravel Framework and using several system support tools including a web browser, XAMPP, MySQL and using the PHP (Hypertext Processor) programming language. This system can make it easier for management to make financial and payroll reports quickly and accurately.